Paleomicrobiology to investigate copper resistance in bacteria: isolation and description of Cupriavidus necator B9 in the soil of a medieval foundry. (27th January 2017) - Gillan, David C.; Van Camp, Camille; Mergeay, Max; Provoost, Ann; Thomas, Nicolas; Vermard, Laurent; Billon, Gabriel; Wattiez, Ruddy
Summary: Remains of a medieval foundry were excavated by archaeologists in 2013 in Verdun (France). Ancient workshops specialized in brass and copper alloys were found with an activity between 13th to 16th c. Levels of Cu, Zn and Pb reached 20000, 7000 and 6000 mg kg −1 (dw), respectively, in several soil horizons. The objective of the present work was to examine the microbial community in this contaminated site. A total of 8–22 10 6 reads were obtained by shotgun metagenomics in four soil horizons. Bioinformatic analyses suggest the presence of complex bacterial communities dominated by Proteobacteria. The structure of the community was not affected by metals, contrary to the set of metal‐resistance genes. Using selective media, a novel strain of Cupriavidus necator (eutrophus), strain B9, was isolated. Its genome was sequenced and a novel metal resistance gene cluster with Hg resistance genes ( merRTPCA ) followed by 24 copper‐resistance genes ( actP, cusCBAF, silP, copK1, copH4QLOFGJH3IDCBARS, copH2H1, copK2 ) was found. This cluster is partly homologous to the cop genes of Cupriavidus gilardii CR3 and C. metallidurans CH34. Proteomics indicated that the four copH genes were differentially expressed: CopH1 and CopH2 were mostly induced by Cd while CopH4 was highly expressed by Cu.